RESEARCH AND ANALYSIS OF MACHINE LEARNING METHODS TO ENSURE THE ECOLOGICAL SECURITY OF ALMATY CITY - Sarzhan Akmaral; Satymbekov Maxatbek (Progress in Science, 2026)
In modern cities, there are acute problems associated with the deterioration of the environmental situation caused by air, water and soil pollution. These factors have a negative impact on the health of the population and the sustainable development of the territories. Almaty, as one of the largest cities in Kazakhstan, faces special challenges related to intensive urbanization and high traffic load. In these circumstances, it is especially important to develop effective methods for assessing environmental risks and predicting possible threats. One of the promising tools for solving this problem are machine learning methods that allow analyzing large amounts of environmental data, identifying hidden patterns and predicting potential risks. The purpose of this study is to study and analyze machine learning methods for ensuring the security of the city of Almaty. This will improve the accuracy of environmental risk assessment and develop preventive measures to reduce the negative impact on the environment.